Ecologycal evaluation of the man-caused impact on the headwater aquatic ecosystems of zhytomyr region (Case study the Gnylopiat River) - Vasilenko, L. O.; Zhukova, O. G.; Honcharenko, A. V. (My University, 2018)
The modern ecological state of aquatic ecosystems of headwaters of Zhytomyr region was researched and characterized for a long, chronological dynamics of water pollution was analyzed, and the main substance-pollutants have been identified. The given results indicate that the main volumes of substancepollutants come into small aquatic ecosystems with insufficiently treated and untreated sewage.
Eкологічна оцінка техногенного впливу на водні екосистеми малих річок житомирської області (на прикладі р. Гнилоп'ять)
Keywords: man-caused impact; ecological safety; ecosystems; headwaters; техногенне навантаження; екологічна безпека; екосистеми; малі річки; 504.453(477.42)